Graphene materials preparation methods have dramatic influence upon their capacitance - Buglione, Lucia (2013)
Graphene related materials are widely expected to play a major role as materials for the construction of supercapacitors. We demonstrate here that graphene oxides prepared by various well-established methods exhibit dramatically different capacitances. We exfoliated graphite oxide sonographically to graphene oxide (GO) and we reduced GO by chemical or electrochemical means to chemically reduced graphene oxide (CRGO) and electrochemically reduced graphene oxide (ERGO); in addition, graphite oxide was thermally exfoliated leading to thermally reduced graphene oxide (TRGO). We found clear dependence of weight specific capacitance upon amount of oxygen containing groups presented on the surface of these graphenes. GO exhibits the lowest and TRGO the highest values of weight specific capacitance.